Applying Uncertain Science to Nature-Based Coastal Protection: Lessons From Shallow Wetland-Dominated Shores - Möller, Iris (Frontiers in Environmental Science, 2019)
Climate change and associated sea-level rise alongside the potential for alterations in the magnitude and frequency of extreme storm events, rapidly rising coastal populations, and a legacy of coastal land reclamation have led to the consideration of nature-based approaches towards coastal flood and erosion protection over recent years. The descriptions of such approaches highlight the flood protection value of natural coastal features but examples of their implementation remain few and far between and nature-based solutions to the rising coastal flood and erosion risk can certainly not (yet) be considered mainstream. One key problem around the implementation of these types of approaches has, arguably, been the relative lack of perceived scientific certainty, amongst stakeholders, surrounding the efficiency with which natural landforms reduce wave action on landward lying structures and the persistence of such landforms in an uncertain future. This makes nature-inclusive approaches less attractive to more traditional engineering-only approaches that rely solely on one ‘hard’ structure with a well-defined impact on waves and a specified design life. Using existing evidence for the coastal protection function of salt marshes, this paper offers a new perspective on this apparent lack of scientific certainty by offering a ‘no-regret’ application of existing science that allows decision makers and coastal planners to implement nature-inclusive approaches to coastal flood and erosion risk reduction measures with greater confidence.